Fungsi pengarahan kepala ruang dalam pelaksanaan discharge plannning perawat di RS PKU Muhammadiyah Yogyakarta - Rosiana Nur Imallah; Anindita Farda Khusnia (STIKes Surya Global Yogyakarta, 2019)
Discharge planning is one indicator of ongoing nursing services that if performed well by the nurses will be able to improve the quality of nursing services and patient satisfaction. One influential factor is the leadership of the head nurse, especially in the function of directing to nurses when carrying out discharge planning. The directional function carried out by the head nurse is in the form of giving motivation, supervision and conflict management. The purpose of this study was to determine the relationship between the function of directional head nurse and the implementation of discharge planning nurses. The study design was descriptive correlational with a cross sectional time approach. The sample in this study were 56 nurses in the inpatient room of PKU Muhammadiyah Yogyakarta Hospital with a sampling technique using simple random sampling. The instrument used was a head nurse directional function questionnaire and discharge planning questionnaire implementation. The data analysis using the Kendall Tau statistical test. The results of this study showed that the assessment of direction function of head nurse were 27 people (48.2%) within adequate category, the implementation of discharge planning were 39 people (69.6%) within good category. The results of the Kendall Tau analysis test were p = 0.002 ( p 0.05). There is a relationship between the function of direction of head nurse to discharge planning nurses.